Interorganizational information acquisition in an innovative SME network: Innovation and information types - Lage, E.; Alturas, B.; Laureano, R. M. S.; Fernandes, A. (International Journal of Business Innovation and Research, 2021)
Information and innovation have been increasingly recognised as sources for firms’ competitive advantage. One of the ways firms have used to acquire these resources is through cooperative relationships, such as networks. This research proposes a conceptual model of antecedents and consequences of the volume of relevant information acquisition and innovation generation in the context of a Portuguese Innovative SME Network. This is an exploratory descriptive study, conducted through a survey of 60 SMEs (34.9% of the population). The results showed that for most firms, the participation on the network does not contribute to the acquisition of relevant information from other firms.